Potential Protective Effects of Pungent Flavor Components in Neurodegenerative Diseases - Fangxin Guo; Xudi Qin; Jian Mao; Yan Xu; Jianping Xie (Molecules)
Neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and Huntington’s disease (HD) have become a major global health burden, but the detailed pathogeneses of neurodegenerative diseases are still unknown, and current treatments are mainly aimed at controlling symptoms; there are no curative treatments for neurodegenerative diseases or treatments for the progressive cognitive, behavioral, and functional impairments that they cause. Studies have shown that some plant extracts with pungent flavor components have a certain neuroprotective effect in neurodegenerative diseases, and their mechanisms mainly involve inhibiting neuronal apoptosis, promoting neuronal regeneration, reducing mitochondrial degeneration, and reducing the production of oxides such as reactive oxygen species in cells, which are of great significance for exploring the treatment of neurodegenerative diseases. In this review, we searched the PubMed database for relevant literature collected in the past 15 years. Finally, we summarized the protective effects of pungent flavor components such as capsaicin, piperine, curcumin, cannabinoids, allicin, and nicotine on the nervous system, focusing on the molecular mechanisms and signaling pathways that they activate. In addition, we also compiled and summarized the laboratory experiments, preclinical experiments, and effects of various pungent flavor components in neurodegenerative diseases. The goal is to further explore their potential as effective drugs for the treatment of neurodegenerative diseases and provide new ideas for further research on the specific protective mechanisms of these substances for the treatment of neurodegenerative diseases and the targets of drug action in the future.